Posterior Shoulder Dislocation Due to an Atypical Trauma Mechanism: A Case Report - Güzel, Şevket Ergun (Orthop J Sports Med, 2014)
OBJECTIVES: A 32 year old man who was admitted to the emergency department with serious pain and absent movement of the right upper extremity due to passing the ball in a basketball game. He had no shoulder dislocation in his medical history. The right shoulder position was flexion and adduction. The shoulder range of motion was restricted and the neurovascular examination was intact. Posterior shoulder dislocation was diagnosed in radiographs.The aim of the study is pointed out an unusual mechanism of the posterior shoulder dislocations which is related microtrauma. The main problem in treatment of this kind of dislocation is correct and timely diagnosis. METHODS: After diagnosing the posterior shoulder dislocation, we reducted the shoulder joint immediately and immobilized in abduction and external rotation with Velpeau bandage. We took radiographs and computerized tomography to confirm the reduction of the joint and diagnose the additional bone pathology. Reverse Hill Sacks lesion was diagnosed. Two weeks later after diagnosing passive range of movement exercises were applied. Magnetic resonance imaging was done to diagnose the additional pathology. RESULTS: There was no spesific finding in radiographs and reverse Hill Sachs lesion and anterior labral tear were determined in magnetic images finding. CONCLUSION: Shoulder joint dislocations are the most seen pathology in the emergency department. On the other hand posterior shoulder dislocations are less common than anterior dislocations, but more commonly missed. Posterior shoulder dislocations are caused by high energy trauma, seizures, electric shocks and microtrauma.